2017
DOI: 10.1016/j.bbmt.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Readmissions after Umbilical Cord Blood Transplantation and Impact on Overall Survival

Abstract: Patients treated with allogeneic hematopoietic stem cell transplantation (SCT) have high rates of readmission, but the incidence after umbilical cord blood transplantation (UCBT) is poorly described. The goal of this study was to identify the incidence and risk factors for readmission after UCBT and the impact of readmission on overall survival (OS). A retrospective review of patients receiving a UCBT at Dana-Farber/Brigham and Women's Hospital between January 1, 2004 and December 31, 2013 was performed. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Spring et al [27] also found that active disease at the time of transplantation and the occurrence of infection during HCT admission is associated with readmission by day +100, and that readmission is independently associated with poor overall survival. A second study by the same group evaluating readmission after UCB transplantation demonstrated similar findings, with inferior survival in those who were readmitted within 100 days [29]. They also found that race and income are associated with readmission within 100 days.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Spring et al [27] also found that active disease at the time of transplantation and the occurrence of infection during HCT admission is associated with readmission by day +100, and that readmission is independently associated with poor overall survival. A second study by the same group evaluating readmission after UCB transplantation demonstrated similar findings, with inferior survival in those who were readmitted within 100 days [29]. They also found that race and income are associated with readmission within 100 days.…”
Section: Discussionmentioning
confidence: 65%
“…Increased hospitalizations, specifically readmissions, have been another recent focus of investigation in allogeneic HCT, as a measure of quality of care, healthcare costs, and predictors of survival [2729]. Given the risks of morbidity and mortality, HCT is typically associated with high rates of hospital readmissions and prolonged hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…These include use of myeloablative or total body irradiation regimens, infections or GVHD during the index HCT admission, higher HCT comorbidity index, Medicaid coverage, and low median income for patients undergoing allo-HCT . In addition, patients undergoing cord blood transplants and patients with acute lymphoblastic leukemia were also at high risk for readmission . Of these, our study identified 3 factors in addition to center volume that were associated with readmission after allo-HCT: higher ECI, cord blood transplantation, and diagnosis of acute lymphoblastic leukemia.…”
Section: Discussionmentioning
confidence: 88%
“…13,15,[21][22][23] In addition, patients undergoing cord blood transplants and patients with acute lymphoblastic leukemia were also at high risk for readmission. 24,25 Of these, our study identified 3 factors in addition to center volume that were associated with readmission after allo-HCT: higher ECI, cord blood transplantation, and diagnosis of acute lymphoblastic leukemia. In addition, our study did not find an association between income and readmission risk.…”
Section: Discussionmentioning
confidence: 96%
“…Сходные данные были получены J. Crombie и соавт. : в их работе риск повторной госпитализации был в 20,6 раза выше при использовании тотального облучения тела [20].…”
Section: Discussionunclassified